Fractionation of biogas plant sludge material improves metaproteomic characterization to investigate metabolic activity of microbial communities. Issue 20 (12th August 2015) - Kohrs, Fabian; Wolter, Sophie; Benndorf, Dirk; Heyer, Robert; Hoffmann, Marcus; Rapp, Erdmann; Bremges, Andreas; Sczyrba, Alexander; Schlüter, Andreas; Reichl, Udo; Jagtap, Pratik; Griffin, Tim; et al.
<x xml:space="preserve">Abstract</x> With the development of high resolving mass spectrometers, metaproteomics evolved as a powerful tool to elucidate metabolic activity of microbial communities derived from full‐scale biogas plants. Due to the vast complexity of these microbiomes, application of suitable fractionation methods are indispensable, but often turn out to be time and cost intense, depending on the method used for protein separation. In this study, centrifugal fractionation has been applied for fractionation of two biogas sludge samples to analyze proteins extracted from (i) crude fibers, (ii) suspended microorganisms, and (iii) secreted proteins in the supernatant using a gel‐based approach followed by LC‐MS/MS identification. This fast and easy method turned out to be beneficial to both the quality of SDS‐PAGE and the identification of peptides and proteins compared to untreated samples. Additionally, a high functional metabolic pathway coverage was achieved by combining protein hits found exclusively in distinct fractions. Sample preparation using centrifugal fractionation influenced significantly the number and the types of proteins identified in the microbial metaproteomes. Thereby, comparing results from different proteomic or genomic studies, the impact of sample preparation should be considered. All MS data have been deposited in the ProteomeXchange with identifier PXD001508 (http://proteomecentral.proteomexchange.org/dataset/PXD001508).